2022
DOI: 10.1038/s41467-022-34137-4
|View full text |Cite
|
Sign up to set email alerts
|

Light activation of Orange Carotenoid Protein reveals bicycle-pedal single-bond isomerization

Abstract: Orange Carotenoid protein (OCP) is the only known photoreceptor which uses carotenoid for its activation. It is found exclusively in cyanobacteria, where it functions to control light-harvesting of the photosynthetic machinery. However, the photochemical reactions and structural dynamics of this unique photosensing process are not yet resolved. We present time-resolved crystal structures at second-to-minute delays under bright illumination, capturing the early photoproduct and structures of the subsequent reac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Recent time-resolved X-ray crystallography experiments 62 revealed a concerted isomerization of two carotenoid single bonds located in the NTD, namely C 6′ –C 7′ and C 8′ –C 9′ ( Fig. 1 ), through the so-called bicycle-pedal mechanism.…”
Section: Discussion and Comparison With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent time-resolved X-ray crystallography experiments 62 revealed a concerted isomerization of two carotenoid single bonds located in the NTD, namely C 6′ –C 7′ and C 8′ –C 9′ ( Fig. 1 ), through the so-called bicycle-pedal mechanism.…”
Section: Discussion and Comparison With Experimentsmentioning
confidence: 99%
“… 15 Furthermore, the experimental conditions employed in ref. 62 could have altered the photocycle of OCP due to the crystal packing. Finally, isomerization at the β 1 ring seems a more likely cause of photoactivation, as (i) the β 1 ring is conserved among different OCP-bound carotenoids, and (ii) it is the location of the H-bond disruption necessary for carotenoid translocation.…”
Section: Discussion and Comparison With Experimentsmentioning
confidence: 99%
“…(1) They can help us better understand the mechanism of photo-activation, which is under intensive study and the object of lively debate ( [3,[35][36][37][38][39] and refs. therein); (2) They provide new information concerning the influence of the surrounding environment on the orange to red activation;…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study by Niziński et al 20 of pump–probe spectra with coverage of the near-IR region has suggested instead that the first intermediate P 1 in the ketocarotenoid translocation mechanism arises not from S* but from the S 1 state proper. Based on evidence from time-resolved X-ray crystal structures, Chukhutsina et al 21 raised the alternative proposal that a “bicycle pedal” configuration 22 of the ketocarotenoid's isoprenoid backbone is produced during the photoactivation reaction.…”
Section: Introductionmentioning
confidence: 99%